Magnetic properties of tetrataenite-rich meteorites II - Nagata, Takesi; Funaki, Minoru; Danon, Jacques A. (1986)
P(論文) Magnetic hysteresis and thermomagnetic characteristics of St. Severin (LL6), Appley Bridge (LL6) and Tuxtuac (LL5) chondrites, which contain tetrataenite in their metallic components, are measured and analyzed in comparison with another tetrataenite-rich chondrite, Yamato-74160 (LL7). The magnetic properties of tetrataenite-rich meteorites are characterized by (a) high magnetic coercive force (H_C) which amounts to 520 Oe for St. Severin and 160 Oe for Appley Bridge, (b) essential flatness up to about 500℃ and then a sharp irreversible drop down to Curie point of the first-run heating thermomagnetic curve. Both characteristic features are broken down to the ordinary features of disordered taenite by a breakdown of tetrataenite structure at elevated temperatures beyond the orderdisorder transition temperature. The natural remanent magnetization (NRM) of tetrataenite-rich meteorites is extremely stable against AF-demagnetization and other magnetic disturbances because of the high magnetic coercivity of tetrataenite. The breakdown processes of ordered tetrataenite structure by heat treatments are experimentally pursued to understand the formation process of tetrataenite phase in meteorites. departmental bulletin paper